A pilot trial of RNS60 in amyotrophic lateral sclerosis. Issue 3 (26th December 2018) - Paganoni, Sabrina; Alshikho, Mohamad J.; Luppino, Sarah; Chan, James; Pothier, Lindsay; Schoenfeld, David; Andres, Patricia L.; Babu, Suma; Zürcher, Nicole R.; Loggia, Marco L.; Barry, Robert L.; Luotti, Silvia; et al.
ABSTRACT: Introduction : RNS60 is a novel immune‐modulatory agent that has shown neuroprotective effects in amytrophic lateral sclerosis (ALS) preclinical models. RNS60 is administered by weekly intravenous infusion and daily nebulization. The objective of this pilot open‐label trial was to test the feasibility, safety, and tolerability of long‐term RNS60 administration in ALS patients. Methods : The planned treatment duration was 23 weeks and the primary outcomes were safety and tolerability. Secondary outcomes included PBR28 positron emission tomography (PET) imaging and plasma biomarkers of inflammation. Results : Sixteen participants with ALS received RNS60 and 13 (81%) completed 23 weeks of RNS60 treatment. There were no serious adverse events and no participants withdrew from the trial due to drug‐related adverse events. There were no significant changes in the biomarkers. Discussion : Long‐term RNS60 administration was safe and well‐tolerated. A large, multicenter, phase II trial of RNS60 is currently enrolling participants to test the effects of RNS60 on ALS biomarkers and disease progression. Muscle Nerve 59 :303–308, 2019